Une mise en cause du contrôle des « nomades » (Tsiganes) relatif à la loi du 16 juillet 1912 : résistances et détournements - Emmanuel Filhol (Criminocorpus)
In order to be allowed to travel, most gypsy families have had to abide by the law the multiple procedures of individual or collective control and identification imposed by the public authorities in France for nearly sixty years (from 1913 to 1970). Various tactical manipulation used by some Gypsies (men and women) towards the police logic of subjugation to which they were confronted cannot be overlooked. They consisted for instance in the non-renewal of anthropometric notebooks, in the concealment of their license plates, or in critical and ironic comments. This article will also address the issue of whether, within the public authorities, those in charge of application of this legislation were critical of it and contributed to limiting excess.